2019
DOI: 10.1002/er.4697
|View full text |Cite
|
Sign up to set email alerts
|

Nonoxidative methane activation, coupling, and conversion to ethane, ethylene, and hydrogen over Fe/HZSM‐5, Mo/HZSM‐5, and Fe–Mo/HZSM‐5 catalysts in packed bed reactor

Abstract: Summary A high abundance of methane and its relatively low price make it an attractive raw feedstock for the production of ethylene, which is in the consumer demand in recent years. Direct catalytic nonoxidative conversion is interesting, because it could be utilized on natural gas well sites. Monometallic and bimetallic Fe and Mo catalysts were prepared for the purpose of the coupling to ethane and ethene. Three supported materials were synthesized with the following loading of metal: 2.5‐wt% Fe, 5.0‐wt% Fe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
(111 reference statements)
1
20
0
Order By: Relevance
“…Figure shows the XRD patterns of commercial and fibrous spherical ZSM‐5 (FZSM‐5)‐supported nickel catalysts. A detailed examination reveals diffractograms within peak range of 2θ = 7‐10° and 22‐25°, which is allotted to ZSM‐5 phase (JCPDS file number 37‐359) . In addition, formation of NiO cubic phase around 2θ = 37.28, 43.2 and 62.5, which corresponds to the (111), (200) and (220) reflections were observed for all supported Ni catalysts .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure shows the XRD patterns of commercial and fibrous spherical ZSM‐5 (FZSM‐5)‐supported nickel catalysts. A detailed examination reveals diffractograms within peak range of 2θ = 7‐10° and 22‐25°, which is allotted to ZSM‐5 phase (JCPDS file number 37‐359) . In addition, formation of NiO cubic phase around 2θ = 37.28, 43.2 and 62.5, which corresponds to the (111), (200) and (220) reflections were observed for all supported Ni catalysts .…”
Section: Resultsmentioning
confidence: 93%
“…Synthesis gas (syngas), a versatile feedstock, has been widely used in the chemical industry as a starting material for the production of liquid energy carriers and high value‐added chemicals . One of the environmentally benign pathways for syngas production is dry reforming of methane (DRM): CH 4 + CO 2 ⇌2CO + 2H 2 , ΔH o 298 K = 260.5 kJ mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of metal promoters is also beneficial for reducing the formation of coke in zeolite channels. For instance, in the work performed by Bajec et al , 52 the addition of Fe to Mo/HZSM-5 catalysts reduces the amount of coke formation, which results in a better stability for the coupling of methane to ethane/ethylene synthesis. The effect of the addition of Fe, Rh, and K on MDA over Mo/HZSM-5 was studied by Ramasubramanian et al , 53 in which the K-promoted catalyst was found to have a better selectivity for benzene (∼50%) after 255 min of reaction ( Fig.…”
Section: Metal/zeolite Catalysts For Nocmmentioning
confidence: 99%
“…Also, HZSM5 has been used for various processes in other research studies. [38][39][40] Consequently, there will be enough reasons and attractiveness to study these series of catalysts. Recently, mesoporous materials have been considered as catalyst support for different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Sharifi et al 37 have investigated the effect of HZSM5 (zeolite support) with different SiO 2 /Al 2 O 3 ratios for HDS and aromatization catalytic processes parallel to each other, and their results showed that a significant increase in the Research Octane Number (RON) from 51.9 to 93 for naphtha feed stock largely covers the medium HDS performance of prepared catalysts. Also, HZSM5 has been used for various processes in other research studies 38‐40 . Consequently, there will be enough reasons and attractiveness to study these series of catalysts.…”
Section: Introductionmentioning
confidence: 99%